2007
DOI: 10.1128/jb.00337-07
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel Bile-Inducible Operon Encoding a Two-Component Regulatory System inLactobacillus acidophilus

Abstract: Lactobacillus acidophilus NCFM is an industrially important strain used extensively as a probiotic culture. Tolerance of the presence of bile is an attribute important to microbial survival in the intestinal tract. A whole-genome microarray was employed to examine the effects of bile on the global transcriptional profile of this strain, with the intention of elucidating genes contributing to bile tolerance. Genes involved in carbohydrate metabolism were generally induced, while genes involved in other aspects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
137
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 134 publications
(144 citation statements)
references
References 40 publications
7
137
0
Order By: Relevance
“…It was found that GOS specifically induced a cluster of genes encoding intracellular proteins involved with galactose and lactose metabolism, notably a LacS permease implicated in GOS transport. The GOS-induced gene cluster was previously identified to be up-regulated by both lactose and bile acids (26,46), validating a role in metabolism of lactose-derived GOS and suggesting an adaptive combination of GIT-evolved traits for energy metabolism and bile tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that GOS specifically induced a cluster of genes encoding intracellular proteins involved with galactose and lactose metabolism, notably a LacS permease implicated in GOS transport. The GOS-induced gene cluster was previously identified to be up-regulated by both lactose and bile acids (26,46), validating a role in metabolism of lactose-derived GOS and suggesting an adaptive combination of GIT-evolved traits for energy metabolism and bile tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…For example, an eight-gene operon encoding a TCS, a transporter, an oxidoreductase, and four hypothetical proteins has been implicated in sensing bile salt in Lb. acidophilus (468). Likewise, the genes encoding multidrug transporters driving extrusion of bile salts are upregulated in Lb.…”
Section: Stress Associated With Intestinal Transitmentioning
confidence: 99%
“…In addition to bsh, other genes (pva and btlB) and the sigma factor B have been shown to contribute to bile resistance in L. monocytogenes EGDe (3). Furthermore, microarray analysis of the bile-induced transcriptome identified genes, including those encoding multidrug resistance (MDR) transporters, chaperone, esterase, and a histidine protein kinase, that were implicated in bile resistance in L. acidophilus NCFM and Lactobacillus reuteri ATCC 55730 (45,62). Genes involved in DNA repair, oxidative response, transcriptional regulation, dGTP hydrolysis, membrane composition, and cell wall synthesis were differentially expressed upon exposure of Enterococcus faecalis or L. plantarum WCFS1 cells to bile (6,7).…”
mentioning
confidence: 99%